Implementasi Mesin Pemotong Singkong Dalam Upaya Pemberdayaan Masyarakat (Fakultas Sains Terapan, 2024)
As a form of implementation of educational outcomes in universities, technological innovation needs to be disseminated to the community. Members of dasawisma RT 07 RW 12, Niten, Nogotirto, Gamping, Sleman are the right targets because they have not applied technology to the process of making cassava chips. The cassava cutting process is still done manually by slicing it with a knife. The purpose of this activity is to introduce and implement cassava cutting machine technology and process cassava into chips of various flavors. The method used is counseling and dissemination of cassava cutting machines and processing cassava chips of various flavors to partners. The result of this service activity is that the partner member of dasawisma RT 07 RW 12, Niten, has known the operating mechanism, maintenance of cassava cutting machines correctly, and is able to diversify cassava preparations into cassava chips of various flavors.The implementation of cassava cutting machine technology is expected to increase the productivity of partner communities.